1989
DOI: 10.1002/mus.880120705
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of skeletal muscle fibers from autologous satellite cells multiplied in vitro. An experimental model for testing cultured cell myogenicity

Abstract: An experimental model used to test in vivo myogenicity of autologous satellite cells multiplied in vitro is described. Free muscle autotransplantation served as the basis and was combined with x-irradiation. Administration of 1500, 2500, and 3500 rad doses 24 hours before or after ischemia showed that inhibition of spontaneous regeneration is dose dependent and more efficient when irradiation was applied before injury. A single dose of 2500 rad before injury resulted in the formation of a cystic structure idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 42 publications
(4 reference statements)
2
41
0
3
Order By: Relevance
“…[34][35][36][37] The mechanism for b-FGF-stimulated proliferation appears to be the advancing of cells from G0 to G1 in the cell cycle. 18,25 Previous studies have also shown that IGF-1 is capable of powerful stimulation of the proliferation and differentiation of myoblasts in vitro. 23,[38][39][40] NGF was the first growth factor to be identified and is known to regulate the development and maintenance of sympathetic and some sensory neurones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36][37] The mechanism for b-FGF-stimulated proliferation appears to be the advancing of cells from G0 to G1 in the cell cycle. 18,25 Previous studies have also shown that IGF-1 is capable of powerful stimulation of the proliferation and differentiation of myoblasts in vitro. 23,[38][39][40] NGF was the first growth factor to be identified and is known to regulate the development and maintenance of sympathetic and some sensory neurones.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 It has already been shown that they are capable of stimulating the growth and protein secretion of many musculoskeletal cells. 17 During muscle regeneration, it is presumed that trophic substances released by the injured muscle activate the satellite cells, [18][19][20][21][22] and in growth and development many growth factors have been shown to be capable of eliciting variable responses from the skeletal muscle. 15,16,23 Preliminary data suggest that individual growth factors play a specific role during muscle regeneration 15,16,[24][25][26][27] and therefore may improve muscle healing.…”
mentioning
confidence: 99%
“…The shielded rats were placed in a Gammacell 40 Cesium-137 Irradiation Unit and exposed to 3,000 rads. This is higher than the dosage of 2,500 rads that has been shown to prevent compensatory hypertrophy in mice and rats Parry, 1992, 1993) and regeneration in autografted rat muscle (Alameddine et al, 1989); however, it is well below the dosage of 12,000 to 18,000 rads at which muscle necrosis became evident in normal rabbit leg muscles (Lewis, 1954).…”
Section: Rat Irradiationmentioning
confidence: 94%
“…They also play a key role in muscle regeneration (Alameddine et al, 1989;Le Grand and Rudnicki, 2007;Mauro, 1961;Shinin et al, 2006;Zammit et al, 2004;Zammit et al, 2006). We observed that MPCs from Sgca-null mice have a reduced proliferative ability in comparison to MPCs from wild-type or mdx dystrophic mice.…”
Section: Introductionmentioning
confidence: 67%